Analysis of open circuit voltage and state of charge of high power lithium ion battery - Jairam Chandra Dutt Mushini; Kuldeep Rana; Mruttanjaya Sanganna Aspalli (Institute of Advanced Engineering and Science, 2022)
Electric vehicles (EVs) are the emerging technologies in the transport sector around the world. EV runs using an electric motor with electricity which is stored in Li-ion batteries (LIBs). Because of its superior qualities LIBs become the market leader for the usage in EVs. With the increased penetration of LIBs in EVs, it is important to monitor the charging and discharging process of the batteries. Accurate estimation of state of charge (SoC) and open circuit voltage (OCV) is essential for the better control of EV. In the present study LIB of 40 Ah nickel manganese cobalt (NMC) cell chemistry has been used for estimation of state of charge at different C-rates as 0.3, 0.5, 1 and 2 C rates. The relationship between the SoC and OCV is nonlinear however relationship between SoC and Ah is linear. Slight rise has been observed in cell terminal temperature at lower C rating at higher C-rating it is found that temperature rise is more (around 10 ℃). Hence, it is important to consider the C-rate of the battery from SoC-OCV curve of the battery. Also, higher C-rate may lead to incorrect estimation of the SoC, reduction in battery life and may lead to potential safety risks.